Colonial conquests and the politics of normalization: The case of the Golan Heights and Northern Cyprus - Ram, Moriel (Political geography, 2015)
The space of exception has been extensively discussed as a location in which governing technologies are deployed through the suspension and manipulation of the norm. The scholarship on the subject has underscored the ways in which various localities can be encamped, which alludes to the dynamic in which spaces of exception can be shaped through the application of various means of sovereign violence that produces new and unpredictable norms. Building on this literature, the article analyzes the ways in which the exception is intentionally used in order to spatially construct the norm. Two case studies are discussed: Israel's occupation of the Golan Heights and the Turkish occupation of Northern Cyprus. The article's main aim is to show how the state of emergency, which provided the justification for deploying exceptional means—occupation and subsequent colonization—was domesticated. By domestication I mean a situation whereby the state of emergency is not fully negated, but rather rearticulated and redeployed in order to reshape the space and transform it so that it is concomitantly both threatening and normal. I go on to show, however, how despite the processes of spatial normalization the state of exception always resurfaces.